THE EFFECT OF TEACHER PERFORMANCE AND STUDENT DISCIPLINE ON STUDENT LEARNING OUTCOMES IN NETWORKING LEARNING AT SMA NEGERI 1 GAMBUT - Siti Darlina (Universitas Lambung Mangkurat, 2022)
This study aims to determine how much influence teacher performance and student discipline have on student learning outcomes in online learning. The research method used is a quantitative method. The research sample consisted of 270 students at SMA Negeri 1 Gambut. The data analysis technique used is correlation analysis and multiple regression analysis with the F test.The results showed that as many as 178 (65.93%) students stated that the teacher's performance in online learning was categorized as good. Student discipline in online learning can be categorized as having a disciplined attitude as many as 128 students (47.41%) and student learning outcomes in online learning are categorized as good because it shows that 179 (66.30%) people have good learning outcomes. The results of the correlation analysis show that teacher performance and student discipline are correlated with student learning outcomes with rxy values of 0.661 and 0.649 respectively. Furthermore, there is a very significant influence between teacher performance variables (X1) and student discipline attitudes (X2) on student learning outcomes (Y) with an F value of 105.991 (p <0.01). The joint correlation index between teacher performance and student discipline was obtained with a value of Ry1,2 = 0.665 with a coefficient of determination R2 of 0.443. The variance of teacher performance and student discipline can explain 44.30% of student learning outcomes in online learning. The implications of the results of this study provide input on the importance of teacher performance and discipline in online learning which of course will have an impact on the learning outcomes to be obtained and the results of this study can be used as a basis or reference for further research.